(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
Marketing is an urgent matter that many organizations seek to achieve, because of its great importance and positive impact on the latter, especially in an environment where competition is intense and the accompanying pressures and threats. The goal of marketing lies in achieving an integrated marketing mix and carrying out marketing activities that contribute to raising The performance rates of the institution and the achievement of excellence and excellence, and considering that marketing is one of the most important factors that contribute significantly to creating and enhancing a competitive advantage and maintaining the continuity of institutions, so our study came to show aspects of the relationship between marketing and competitive advantage by shedding light on the Ceramics Corporation - sartaf - as a model that works to market its products As a way to enable it to survive in the competitive crowd that characterizes the environment in which it is located.